Financial reporting, tax costs, and book-tax conformity - Guenther, David A.; Maydew, Edward L.; Nutter, Sarah E. (Journal of Accounting and Economics, 1997)
We investigate the role of book-tax conformity in firms' financial reporting activities using a unique set of publicly traded firms that were forced to switch for tax purposes from the cash method to the accrual method. Prior to the mandated change, little trade-off existed between tax planning and financial reporting goals for these firms. After the change, recognition criteria for tax and financial reporting purposes became more alike, increasing the trade-off between financial reporting and tax objectives. Our results suggest that required use of the accrual method for tax purposes causes firms to defer income for financial statement purposes.